2021
DOI: 10.3390/molecules26164817
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities and Molecular Docking of Novel Sulfone Biscompound Containing Bioactive 1,2,3-Triazole Moiety

Abstract: In this study, a new synthetic 1,2,3-triazole-containing disulfone compound was derived from dapsone. Its chemical structure was confirmed using microchemical and analytical data, and it was tested for its in vitro antibacterial potential. Six different pathogenic bacteria were selected. MICs values and ATP levels were determined. Further, toxicity performance was measured using MicroTox Analyzer. In addition, a molecular docking study was performed against two vital enzymes: DNA gyrase and Dihydropteroate syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Over the past few years, compounds containing thiazole and/or thiadiazole scaffold are attractive to medicinal chemistry due to their unique chemical properties and diversity of the biological activities [20–25] . Therefore, they have therapeutic effects against several diseases such as antimalarial, antimicrobial, antiproliferative agents and anti‐inflammatory [26–30] besides their significant with various fungicidal activities [31,32] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, compounds containing thiazole and/or thiadiazole scaffold are attractive to medicinal chemistry due to their unique chemical properties and diversity of the biological activities [20–25] . Therefore, they have therapeutic effects against several diseases such as antimalarial, antimicrobial, antiproliferative agents and anti‐inflammatory [26–30] besides their significant with various fungicidal activities [31,32] .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Over the past few years, compounds containing thiazole and/or thiadiazole scaffold are attractive to medicinal chemistry due to their unique chemical properties and diversity of the biological activities. [20][21][22][23][24][25] Therefore, they have therapeutic effects against several diseases such as antimalarial, antimicrobial, antiproliferative agents and anti-inflammatory [26][27][28][29][30] besides their significant with various fungicidal activities . [31,32] In addition, many scientific reported have also demonstrated that the sulfonamide moiety itself possess interesting pharmacological activities and therapeutic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies indicated that extended spectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE) and Pseudomonas aeruginosa can persist in the presence of several antibiotics through biofilm accumulation. In this way, the high resistance of different pathogens is increasingly identified as the cause for predominant causative pathogens in patients due to antibiotic misuse [1][2][3]. Consequently, the investigation of new heterocyclic compounds to encounter antibiotic resistance is among the most important aspects of preliminary pharmaceutical research.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, solvent-free organic synthesis is of great interest to introduce classical methods that are safer, cleaner, and easier to perform. Reactions without any solvent support can be employed with significant increases in reactivity and selectivity [2,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Benzimidazole derivatives represent an important heterocyclic class of active therapeutic agents because of their wide spectrum of biological and pharmaceutical applications including antibacterial, antifungal, antiviral, anticancer, antidiabetic, anticonvulsant, and anti-HIV agents [ 5 , 6 ]. In addition, 1,2,3-triazoles have attracted a great deal of interest from medicinal chemists in the design and development of potential drug candidates due to their high pharmacological properties such as antimicrobial, antitubercular, CNS depressant, and antihypertensive activities [ 7 , 8 , 9 , 10 , 11 , 12 ]. They have diverse applications in drug development for the treatment of some diseases including cancer, inflammation, malaria, and tuberculosis [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%